Makna Doa Berkat Di Akhir Ibadah Kristen Berdasarkan Bilangan 6:23-27 Dan 2 Korintus 13:13 - Jundo Parasian Siregar (Jurnal Shema, 2025)
This study explores the meaning of the prayer of blessing at the end of worship, as practiced by many churches. The prayer of blessing is based on Numbers 6:24-26 and 2 Corinthians 13:13. Previous research found that some prayers of blessing include additional phrases. Furthermore, some prayers are delivered incompletely or in reverse order, not in accordance with the biblical references. Furthermore, the understanding of the person delivering the blessing and the recipient is often out of sync. This paper uses theological research, a qualitative biblical theology approach, because its purpose is to discover the meaning of the biblical text. The results show that the prayer of blessing is "appropriate" for ministers who dedicate themselves fully to God. The prayer of blessing at the end of worship is not directly related to material things or their abundance. The meaning of the prayer of blessing is the assurance of God's presence, which inspires confidence. It emphasizes the grace of the Lord Jesus, the love of God, and the fellowship of the Holy Spirit. The purpose is to live according to the guidance of the Holy Spirit. Therefore, the prayer of blessing at the end of each service deserves to be believed and lived out.